The Use of Eye-Tracking Technology in Mathematics Education: A Mapping Study with Bibliometric Analysis - Farman; Siswono, Tatag Y. E.; Lukito, Agung; Dewi, Ratna Sari; Hali , Fitriyani; Herlina (Ital Publication, 2025)
This study aims to identify trends, domains, and research topics of eye-tracking methodology in mathematics education published in Scopus-indexed journals. A systematic mapping study with bibliometric was employed to investigate the field. The analysis identified 119 eye-tracking studies in mathematics education published between 2013 and 2023, reflecting fluctuating publication trends. In this period, 333 authors, 78 sources, 156 organizations, and 38 countries contributed to the field. Schindler authored the most documents, while Germany and the United States recorded the highest output. The most cited work was by Cortina et al., and the International Journal of Science and Mathematics Education was the most frequently cited journal. Collaborations analysis identified Brockmole and Hannula as the most collaborative authors, and the University of Helsinki as the most active institution. Topic and domain analysis showed that the studies primarily focused on numbers and arithmetic, problem-solving, reasoning, individual differences, mathematical anxiety, creativity, mathematical representation, multimedia in learning, embodied cognition, mathematics learning, learning difficulties, geometry, and preschool mathematics. The findings suggest that several mathematical domains remain underexplored, offering opportunities for further eye-tracking research in mathematics education.